2007
DOI: 10.1002/ptr.2320
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory activity of biopolymeric fraction BOS 2000 from Boswellia serrata

Abstract: Oral administration of BOS 2000 (1-10 mg/kg) elicited a dose related increase in the delayed hypersensitivity reaction (early 24 h and delayed 48 h) in mice. It also stimulated the IgM and IgG titre expressed in the form of plaques (PFC) and complement fixing antibody titre. The concentration of cytokines (IL-4, IFN-gamma and TNF-alpha) in serum with respect to T cell interactions, i.e. (CD4/CD8) and the proliferation of lymphocytes were significantly increased at 10 mg/kg compared with the control. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…After 72 h, 20 µL of MTT solution (5 mg/mL) were added to each well and incubated for 4 h. The plates were centrifuged (1400 × g, 5 min) and the untransformed MTT was removed carefully by pipetting. To each well, 100 µL of a DMSO working solution (192 µL DMSO with 8 µL 1 M HCl) was added, and the absorbance was evaluated in an ELISA reader at 570 nm after 15 min (Khajuria et al, 2008[16]).…”
Section: Methodsmentioning
confidence: 99%
“…After 72 h, 20 µL of MTT solution (5 mg/mL) were added to each well and incubated for 4 h. The plates were centrifuged (1400 × g, 5 min) and the untransformed MTT was removed carefully by pipetting. To each well, 100 µL of a DMSO working solution (192 µL DMSO with 8 µL 1 M HCl) was added, and the absorbance was evaluated in an ELISA reader at 570 nm after 15 min (Khajuria et al, 2008[16]).…”
Section: Methodsmentioning
confidence: 99%
“…Other adjuvants such as monophosphoryl lipid A, ISCOMS, QS-21 a purified saponin from bark of Quillaja saponaria Molina, and Syntex Adjuvant Formulation (SAF) are being investigated for development of better and safer adjuvants (14). Plant based immunomodulators are being considered as one option (15)(16)(17) (18)(19)(20)(21). Attempts to organize adjuvants in grouped categories in order to facilitate adjuvant selection have sometimes been difficult because of multiple and overlapping biological effects of many adjuvants.…”
Section: Types and Classification Of Adjuvantsmentioning
confidence: 99%
“…Extract of Boswellia Serrata or β-boswellic acid has been reported to inhibit hypersensitivity reactions by regulating both the humoral and cellular immune systems They decrease primary antibody synthesis, inhibit polymorphonuclear leukocyte proliferation and infiltration, enhance the phagocytotic function of macrophages, and suppress the classical and alternate complement pathways [254,255] and suppress the inflammation process, one of the critical pathological features in asthma. It has been shown that β-boswellic acid inhibits the production of proinflammatory cytokines, including TNF, IL-1, IL-2, IL-6, IL-12 and IFN-γ by suppressing the activation of NF-κB [256].…”
Section: Boswellia Serratamentioning
confidence: 99%